Beginning programming with Java for dummies - Burd, Barry (--For dummies., 2014)
Beginning Programming with Java For Dummies, 4th Edition is a comprehensive guide to learning one of the most popular programming languages worldwide. This book covers basic development concepts and techniques through a Java lens. You'll learn what goes into a program, how to put the pieces together, how to deal with challenges, and how to make it work. The new Fourth Edition has been updated to align with Java 8, and includes new options for the latest tools and techniques. Java is the predominant language used to program Android and cloud apps, and its popularity is surging as app demand rises. Whether you're just tooling around, or embarking on a career, Beginning Programming with Java For Dummies, 4th Edition is a great place to start. Step-by-step instruction, easy-to-read language, and quick navigation make this book the perfect resource for new programmers. You'll begin with the basics before moving into code, with simple, yet detailed explanations every step of the way. Topics include: Learn the language with sample programs and the Java toolkit; Familiarize yourself with decisions, conditions, statements, and information overload; Differentiate between loops and arrays, objects and classes, methods and variables. The book also contains links to additional resources, other programming languages, and guidance as to the most useful classes in the Java API. If you're new to programming languages, Beginning Programming with Java For Dummies, 4th Edition provides the instruction and practice you need to become a confident Java programmer.--Publisher description.